1997
DOI: 10.1177/0146167297235001
|View full text |Cite
|
Sign up to set email alerts
|

An Item Response Theory Analysis of the Rosenberg Self-Esteem Scale

Abstract: The Rosenberg Self-Esteem Scale, a widely used self-report instrument for evaluating individual self-esteem, was investigated using item response theory. Factor analysis identified a single common factor, contrary to some previous studies that extracted separate Self-Confidence and Self-Depreciation factors. A unidimensional model for graded item responses was fit to the data. A model that constrained the 10 items to equal discrimination was contrasted with a model allowing the discriminations to be estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
365
0
17

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 617 publications
(395 citation statements)
references
References 24 publications
13
365
0
17
Order By: Relevance
“…The Self-Esteem Scale (SES) was used to measure a participant's general sense of self-worth and self-acceptance [24]. It consists of 10 statements.…”
Section: ) Self-esteemmentioning
confidence: 99%
“…The Self-Esteem Scale (SES) was used to measure a participant's general sense of self-worth and self-acceptance [24]. It consists of 10 statements.…”
Section: ) Self-esteemmentioning
confidence: 99%
“…This scale assesses the overall selfesteem based on statements from respondents regarding positive and negative feelings. Previous studies have reported alpha coefficients ranging from 0.72 to 0.88 for the scale (Gray Little, Williams, & Hancock, 1997). A 7-week test-retest reliability of 0.61 was also obtained for the scale (Byrne, 1983).…”
Section: Methodsmentioning
confidence: 59%
“…29 This measure has demonstrated adequate reliability and validity. 30 It has also been translated into several languages and has demonstrated good psychometric properties in 53 countries, including Latin American countries, such as Argentina, Bolivia, Brazil, Chile, Mexico, and Peru. 28 The internal consistency of this scale in the present study was good (α = 0.86).…”
Section: Rosenberg Self-esteem Scalementioning
confidence: 99%